PENGARUH PEMBERIAN KOMPENSASI, PERATURAN YANG PASTI, SERTA PENGAWASAN PIMPINAN TERHADAP PENINGKATAN DISIPLIN KERJA GURU DI MAN 3 LANGKAT - Az-Zahra, Farah Witri; Wakhyuni, Emi; Taufik, Akhmad (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aimed to investigate the influence of compensation, regulations, and supervision on the work discipline of teachers at MAN 3 Langkat. The population of this research comprised all civil servant and PPPK teachers at MAN 3 Langkat, totaling 40 employees. The sample size taken was 40 respondents, using a saturated sampling technique. The research was conducted in 2024. Data collection was carried out using questionnaires to produce primary quantitative data measured with a Likert scale, which was then processed with SPSS 24 using multiple linear regression methods. The results showed that compensation, regulations, and supervision, both partially and simultaneously, had a positive and significant effect on the work discipline of teachers at MAN 3 Langkat. The t-test (partial) results indicated that compensation had a regression value of 0.332, t-value = 3.697, and significance = 0.001. Regulations had a regression value of 0.365, t-value = 5.242, and significance = 0.000. Supervision had a regression value of 0.220, t-value = 3.456, and significance = 0.001. The F-test (simultaneous) results showed an F-value = 226.049 and significance = 0.000. The t-table value was 2.028, and the F-table value was 2.866, thus t-value > t-table and F-value > F-table with a significance value > 0.05, meaning Ha was accepted and Ho was rejected. The hypotheses were proven true and acceptable as the research results were consistent with the hypotheses. Regulations were the most dominant variable affecting work discipline, with a t-value of 5.242. Approximately 94.5% of work discipline could be explained and obtained from compensation, regulations, and supervision, while the remaining was due to other factors. Work discipline had a very strong relationship with compensation, regulations, and supervision.